Gestión ambiental : ¿estrategia para el desarrollo sostenible? (2005)
ABSTRACT: The development as utopia and the sustainable development as possible ideal are, nowadays, a place and a common purpose for the humanity. The environmental problems, product of the troubled relationship among the society and the nature, in a given territory, are one of the greater obstacles to reach more and better levels of sustainable development. To aspire, accordingly, to elevate the present levels of sustainable development of a population located in a territory, in a period of time, requires among others things, to attend in an adequate way the environmental problems derived from its mutual relation with the natural elements presents in a context, that is to say, identify them, value them, prevent them and correct them if that is the case. To attend the environmental problems is arranged, in Colombia, of a powerful legal instrument, derived from the constitutional mandate of 1991: The Environmental ordering of the Territory, consecrated in the laws 99 of 1993 and 288 of 1997, of obligatory fulfillment for the municipalities, districts and native territories. Nevertheless, as legal instrument, favors the attention of the problems conceiving the ordering of the territory as an effective action for the promotion of the territorial sustainable development, from the definition of the uses, priorities and tendencies in the management of the ground; but it doesn´t possess the enough strength for the attention of the environmental problems. It permits the showing up of a dynamic and promoter strategy of actions that make possible to attend them in a right way: the territorial environmental management. So it is concluded that if the environmental management makes dynamic the territorial environmental ordering and this one, at the same time, is an appropriate instrument to attend the environmental problems, main obstacle to reach better levels of sustainable development, then, the environmental management is a strategy to reach the territorial sustainable development.